Sistem Informasi Monitoring Data Obat di Puskesmas Bontoperak Kabupaten Pangkajene dan kepulauan - Tamus Bin Tahir; Muhammad Rais; Irwan Syarif; Mochammad Apriyadi Hadi Sirad; Rosihan Aminuddin (Patria Artha Technological Journal, 2022)
This research aims to design and create applications that can monitor drug data, namely incoming drug data, outgoing drugs, drug stocks and report making. The research method used is R&D because researchers want to produce products and test the effectiveness of the products in order to function. While the pngujian method on this system uses black box testing which aims to perform tests based on system details such as the appearance, functions and suitability of the function flow of the system. From the results of system testing, all functions in the system can function properly so as to help the performance of the officers in the health center, especially those who handle drug data. The drug data monitoring information system has been successfully designed to be used by the Head of Puskesmas, warehouse officers, and pharmacy officers. Drug warehouse officers are given the facility to enter data on sources of funds, suppliers, drugs and conduct drug transactions in and out of the warehouse. Furthermore, pharmacy officers can enter patient data and make drug transactions out at the pharmacy. As for the Head of puskesmas has facilities to be able to see the report and then print it.